Reconfigurable active frequency selective surface for ultra‐wideband applications. Issue 7 (18th March 2020) - Zhao, Yulin; Fu, Jiahui; Liang, Zhiming; Wang, Zhefei; Zhang, Zhiyi; Lv, Bo; Chen, Wan
Abstract: A reconfigurable active frequency selective surface (AFSS) with ultra‐wideband (UWB) characteristics is presented in this article. The proposed AFSS consists of a periodic array of three metal layers and two dielectric layers. PIN diodes are arranged on the top and bottom metal layers which can rebuild the function of AFSS. The transmission bandwidth of the AFSS with OFF‐state diodes is 8 to 12.5 GHz with a fractional bandwidth of 44%, and the transmission coefficient of the FSS with ON‐state diodes is lower than −10 dB from 2 to 18 GHz. Additionally, the AFSS is angular stable and polarization‐insensitive for both transverse electric and transverse magnetic polarizations. The simulation results show that the proposed AFSS is an effective candidate for radome applications.